The Role of a Notary in Changing the Name of a Limited Liability Company - Detkri Badhiron; Umar Ma'ruf (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2021)
This research aims to know and analyze the factors that cause PT. Mega Transformation Indonesia turned into PT. Djaja Bangun Rahardja, besides that this research is also to find out and analyze the role of the Notary in changing PT. Mega Transformation of Indonesia into PT. Djaja Bangun Rahardja was connected with Act No. 40 of 2007 concerning Limited Liability Companies and the last one was to identify and analyze the process of obstacles and solutions in the process of changing PT. Mega Transformation Indonesia into PT. Djaja Bangun Rahardja is associated with Act No. 40 of 2007 concerning Limited Liability Companies. The approach method in this research is empirical juridical. The juridical approach (law is seen as a norm or das sollen), because in discussing the problem this research uses legal materials (both written law and unwritten law or both primary legal materials and secondary legal materials). Empirical approach (law as a social, cultural or das sein reality), because in this study primary data obtained from the field were used. So, the empirical juridical approach in this study means that in analyzing the problem, it is done by combining legal materials (which are secondary data) with primary data obtained in the field, namely about how the role of Notaries requires empirical research on Notaries who process changes in names of shareholders and changes to the Board of Directors. The specifications used in this research are descriptive analytical, which is intended to provide data as accurate as possible about a situation or other symptoms. Because this research is expected to provide a detailed, systematic and comprehensive description of the role of a Notary in processing the name change of a limited liability company. The data required includes Primary data is data obtained from the field, data obtained from respondents. Respondents are people or people who provide answers to questions from researchers. Secondary data is data obtained from or derived from library materials, secondary data collected in this study include primary legal materials, secondary legal materials and tertiary legal materials. In discussing the subject matter and analyzing the data that has been obtained, the authors use all the information and data that have been obtained, both primary data and secondary data. Then the writer analyzes qualitatively which is then presented descriptively.